Behavioral Economics Interventions to Improve Outpatient Antibiotic Prescribing for Acute Respiratory Infections: a Cost-Effectiveness Analysis - Gong, Cynthia L. (J Gen Intern Med, 2018)
BACKGROUND: Behavioral economics interventions have been shown to effectively reduce the rates of inappropriate antibiotic prescriptions for acute respiratory infections (ARIs). OBJECTIVE: To determine the cost-effectiveness of three behavioral economic interventions designed to reduce inappropriate antibiotic prescriptions for ARIs. DESIGN: Thirty-year Markov model from the US societal perspective with inputs derived from the literature and CDC surveillance data. SUBJECTS: Forty-five-year-old adults with signs and symptoms of ARI presenting to a healthcare provider. INTERVENTIONS: (1) Provider education on guidelines for the appropriate treatment of ARIs; (2) Suggested Alternatives, which utilizes computerized clinical decision support to suggest non-antibiotic treatment choices in lieu of antibiotics; (3) Accountable Justification, which mandates free-text justification into the patient’s electronic health record when antibiotics are prescribed; and (4) Peer Comparison, which sends a periodic email to prescribers about his/her rate of inappropriate antibiotic prescribing relative to clinician colleagues. MAIN MEASURES: Discounted costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios. KEY RESULTS: Each intervention has lower costs but higher QALYs compared to provider education. Total costs for each intervention were $178.21, $173.22, $172.82, and $172.52, and total QALYs were 14.68, 14.73, 14.74, and 14.74 for the control, Suggested Alternatives, Accountable Justification, and Peer Comparison groups, respectively. Results were most sensitive to the quality-of-life of the uninfected state, and the likelihood and costs for antibiotic-associated adverse events. CONCLUSIONS: Behavioral economics interventions can be cost-effective strategies for reducing inappropriate antibiotic prescriptions by reducing healthcare resource utilization.